CALIBER: a phase II randomized feasibility trial of chemoablation with mitomycin‐C vs surgical management in low‐risk non‐muscle‐invasive bladder cancer. (3rd April 2020) - Mostafid, A. Hugh; Porta, Nuria; Cresswell, Joanne; Griffiths, Thomas R.L.; Kelly, John D.; Penegar, Steven R.; Davenport, Kim; McGrath, John S.; Campain, Nicholas; Cooke, Peter; Masood, Shikohe; Knowles, Margaret A.; et al.
Abstract : Objectives: To evaluate the activity of intravesical mitomycin‐C (MMC) to ablate recurrent low‐risk non‐muscle‐invasive bladder cancer (NMIBC) and assess whether it may enable patients to avoid surgical intervention for treatment of recurrence. Patients and Methods: CALIBER is a phase II feasibility study. Participants were randomized (2:1) to treatment with four once‐weekly MMC 40‐mg intravesical instillations (chemoablation arm) or to surgical management. The surgical group was included to assess the feasibility of randomization. The primary endpoint was complete response to intravesical MMC in the chemoablation arm at 3 months, reported with exact 95% confidence intervals (CIs). Secondary endpoints included time to subsequent recurrence, summarized by Kaplan–Meier methods. Results: Between February 2015 and August 2017, 82 patients with visual diagnosis of recurrent low‐risk NMIBC were enrolled from 24 UK hospitals (chemoablation, n = 54; surgical management, n =28). The median follow‐up was 24 months. Complete response at 3 months was 37.0% (20/54; 95% CI 24.3–51.3) with chemoablation and 80.8% (21/26; 95% CI 60.6–93.4) with surgical management. Amongst patients with complete response at 3 months, a similar proportion was recurrence‐free by 12 months in both groups (84%). Amongst those with residual disease at 3 months, the 12‐month recurrence‐free proportion was lower in the surgical management group (40.0%) than in the chemoablation group (84%). Recruitment stopped early as chemoablation did not meet the prespecified threshold of 45% complete responses at 3 months. Conclusion: Intravesical chemoablation in low‐risk NMIBC is feasible and safe, but did not demonstrate sufficient response in the present trial. After chemoablation there may be a reduction in recurrence rate, even in non‐responders, that is greater than with surgery alone. Further research is required to investigate the role and optimal schedule of neoadjuvant intravesical chemotherapy prior to surgery for NMIBC.